2022
DOI: 10.1371/journal.pone.0260982
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based meteorological drought indicator to support food security in Java Island

Abstract: A meteorological drought refers to reduced rainfall conditions and is a great challenge to food security. Information of a meteorological drought in advance is important for taking actions in anticipation of its effects, but this can be difficult for areas with limited or sparse ground observation data available. In this study, a meteorological drought indicator was approached by applying the Standardized Precipitation Index (SPI) to satellite-based precipitation products from multiple sources. The SPI based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Although some level of consistency between data products reported for GPCC, PERSIANN‐CDR and CHIRPS (Wei et al, 2019) and between GPCC, CRU and the University of Delaware (Wei et al, 2020) precipitation products in representing drought events in most of China, GPCC outperformed the others and data products showed heterogeneity in representing drought events over the plateau area. On the other hand, CHIRPS and TRMM showed better performance over PRESIANN precipitation data in capturing the occurrence of drought in Java Island (Siswanto et al, 2022). In the East African Lake Victoria Basin, CHIRPS was superior to PERSIANN‐CDR in representing the historical drought events (Das et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some level of consistency between data products reported for GPCC, PERSIANN‐CDR and CHIRPS (Wei et al, 2019) and between GPCC, CRU and the University of Delaware (Wei et al, 2020) precipitation products in representing drought events in most of China, GPCC outperformed the others and data products showed heterogeneity in representing drought events over the plateau area. On the other hand, CHIRPS and TRMM showed better performance over PRESIANN precipitation data in capturing the occurrence of drought in Java Island (Siswanto et al, 2022). In the East African Lake Victoria Basin, CHIRPS was superior to PERSIANN‐CDR in representing the historical drought events (Das et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted during the last few years to evaluate the drought monitoring performance of global and quasi‐global precipitation products at different spatial scales and parts of the world (e.g., Chen et al, 2022; Das et al, 2022; Golian et al, 2019; Guo et al, 2016; Katiraie‐Boroujerdy et al, 2016; Pandey et al, 2020; Siswanto et al, 2022; Wei et al, 2019; Yan et al, 2018; Zhao & Ma, 2019; Zhong et al, 2019). For example, Zhao and Ma (2019) have found discrepancies between four precipitation products in representing the spatiotemporal characteristics of drought across the world.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on Java Island [8] discovered that, in contrast to the SPEI, the SPI predicted drought severity with an abnormally high estimate. Another study also found that satellitebased precipitation monitoring demonstrates the possibility of anticipating meteorological drought conditions in Java and mitigating their impacts several months in advance [6].…”
Section: Introductionmentioning
confidence: 89%
“…Data from 2014 to 2018 in Central Java reveal that the link between yearly rainfall and the drought-affected area is greater than the correlation between rainfall and the flood-affected area [5]. The El Nino and a positive-phase Indian Ocean Dipole (IOD) altered meteorological droughts in the eight main rice-producing regions in Java [6].…”
Section: Introductionmentioning
confidence: 99%
“…Java Island is chosen as domain for this study since Java Island is the main rice-producing island in Indonesia, as the 8.1 million hectares of rice farming land in Indonesia, about 40% of which are settled in the Java Island area [5,6]. This is due to the fertile soil on the island of Java because it is an area surrounded by active volcanoes, which is one of the factors supporting soil fertility [7].…”
Section: Introductionmentioning
confidence: 99%